To the Question of Christian Personalism of Markellin Olesnitskyi - Viktor Kozlovskyi (Наукові записки НаУКМА: Філософія та релігієзнавство, 2019)
The article examines the peculiarities of Christian personalism of Markellin Olesnitskyi, a professor at the Kyiv Theological Academy, the author of insightful works on Christian ethics, psychology, and pedagogy. There is an analysis of the conceptual approaches of the Kyiv scholar to the concept of the human individuality. Attention is drawn to those conceptual influences which contributed to the personalistic position of Olesnitskyi. They were G. Leibniz and F. Schleiermacher. In his studies, the Kyiv scholar always took into account the ideas of these thinkers concerning a human and his or her individuality. In particular, he liked the idea of Leibniz, who considered a individuality as a “complete whole”, a certain singularity, the conceptual definition of which does not require the treatment of general entities (type and genus). Also, he was inspired by the ideas of Schleiermacher, for whom individuality was a special modification of mankind. Schleiermacher thought that the human nature could not be considered separately from the individual selfexpression, cultural diversity of people. It was discovered that the Kyiv scholar needed the analysis of the human individuality for the research of the human personality that was considered as an individual having own personality. This makes it possible to consider the personality as a “being-for-itself”, as an independent being that is capable of making a moral choice. Olesnitskyi treats a person as a subjective focus of reason, will, and feelings, as well as the basis of history. In the article, one can see how the Kyiv professor treats attempts to implement mathematical and statistical methods to the study of social life. It is worth mentioning that those attempts were innovative for that period of time. The article includes an analysis of the standpoints of famous European researchers, among whom there were J. Süssmilch, A. Quetelet, H. Buckle, A. Wagner, and A. Oettingen. They demonstrated the efficiency of these methods application for both the analysis of the social and economic life of society and the study of his moral life (A. Oettingen called this phenomenon “moral statistics”), which made possible the appearance of social ethics. One can notice the positive as well as the critical attitude of the Kyiv acholar towards the already-mentioned research.